Steady-State PERG Adaptation Reveals Temporal Abnormalities of Retinal Ganglion Cells in Treated Ocular Hypertension and Glaucoma - Tommaso Salgarello; Andrea Giudiceandrea; Grazia Maria Cozzupoli; Martina Cocuzza; Romolo Fedeli; Donato Errico; Antonello Fadda; Filippo Amore; Marco Sulfaro; Epifanio Giudiceandrea; Matteo Salgarello; Stanislao Rizzo; et al. (Diagnostics)
Background/Objectives: This study investigates adaptive changes in long-lasting pattern electroretinogram (PERG) responses in ocular hypertension (OHT) and open-angle glaucoma (OAG) patients, and in healthy subjects. Methods: Sixty consecutive individuals were recruited, including 20 OHT, 20 OAG, and 20 normal subjects. All participants underwent comprehensive ophthalmologic examination, 30–2 perimetry, and retinal nerve fiber layer imaging. Steady-state (7.5 Hz) PERGs were recorded over approximately 2 min, in response to 90% contrast alternating gratings within a large field size. The recordings were acquired into a sequence of 10 averages (packets), lasting 10 s each, following a standardized adaptation paradigm (Next Generation PERG, PERGx). Key outcome measures included PERGx parameters reflecting response amplitude and phase changes over time. Results: The PERGx grand average scalar amplitude, a surrogate of ordinary PERG, was significantly reduced in both OHT and OAG groups compared to normal subjects (p < 0.01). In contrast, minimal adaptation changes were noted in PERGx amplitude among all groups. The PERGx phase exhibited a progressive decline over time, with consistent delays of approximately 20 degrees across all groups. Angular dispersion of the PERGx phase increased significantly in OHT patients compared to normal subjects (p < 0.05). An inverse relationship was observed between PERGx angular dispersion and treated intraocular pressure, specifically in OHT patients. Conclusions: The findings suggest that both OHT and OAG eyes may exhibit temporal abnormalities in PERG adaptation, potentially indicating early dysfunction in retinal ganglion cell activity. Translational Relevance: PERGx phase changes may have significant implications for glaucoma early detection and management.